The maintenance of Malaysia's minority languages - Mohamed Ali, Haja Mohideen (2010)
Malaysia, especially the states of Sabah and Sarawak are home to numerous indigenous languages. According to the Ethnologue Report for Malaysia (2009), Sabah is said to have 52 and Sarawak 46 languages. But among these many languages, many are spoken by a small population. These are in danger of facing extinction due to migration, attitudinal, social, educational and economic factors, mainly. This situation is similar to the many languages which are dying today worldwide. Since the Malay language (Bahasa Malaysia) is a potent force in bringing together the various Bumiputra and Muslim groups, the fate of native languages of these disparate groups is uncertain or worse doomed to die. However, measures by speakers of indigenous languages who comprise a sizeable number, for example, in the case of Sabah, Kadazan, Bajau, Bisaya and Murut languages may still be saved if they are maintained through concerted efforts by the affected communities and if government agencies help to play their part. This paper will discuss the various practical steps that may be undertaken by concerned individuals, the elders and leaders of the target minority communities themselves, language scholars and the state and federal governments to help maintain the minority indigenous languages, with particular emphasis on those from Sabah and Sarawak.